Effect of different water tensions in the soil on the nutritional absorption of macroelements in the cultivation onion (Allium cepa) c.v. Álvara in a protected environment - Chavarría-Vidal, Adrián (2024)
Moisture in the soil can be studied in several ways, but a fundamental way is the suction with which the water is retained. The retention exerted by the soil or soil substrate in its pore space on moisture is a representation of the amount of negative pressure that the plant must exert through its roots to suck the water found in it. If this magnitude of suction is high, then it can become restrictive to plant growth. The water found in the porous space, usually called soil solution, is not found in a pure state, but is normally found in solution and has chemical elements that the plant may or may not need for its growth and development, whereby absorbing said water, also absorbs the chemical elements in solution. For these reasons, 4 treatments were planted which consisted of maintaining the soil in ranges of 5 - 15 kPa, 15 - 25 kPa, 25 - 35 kPa and 35 - 45 kPa of water retention and quantifying the nutritional absorption. With respect to nutritional uptake which was present in the soil substrate, Nitrogen (N) and Phosphorus (P) showed significant difference (Pvalue < 0,05) in the soil water suction ranges of 5 - 15 kPa, 15 - 25 kPa, 25 - 35 kPa and 35 - 45 kPa and Potassium (K), Calcium (Ca), Magnesium (Mg) and Sulfur (S) showed significant difference (Pvalue < 0,05) in the 5 - 15 kPa, 15 - 25 kPa, 25 - 35 kPa ranges but showed no significant difference (Pvalue > 0,05) in the 25 - 35 kPa and 35 - 45 kPa ranges. Therefore, it was concluded that there is an inverse effect of the increase of water suction in the soil on the decrease of nutritional absorption capacity.